Study on the Customization of Robotic Arms for Spray-Coating Production Lines - Chao-Chung Liu; Jun-Chi Liu; Chao-Shu Liu (Machines)
This paper focuses on the design and development of a customized 7-axis suspended robotic arm for automated spraying production lines. The design process considers factors such as workspace dimensions, workpiece sizes, and suspension positions. After analyzing degrees of freedom and workspace coordinates, 3D modeling ensures the arm can reach designated positions and orientations. Servo motors and reducers are selected based on load capacity and speed requirements. A suspended body method allows flexible use within the workspace. Kinematics analysis is conducted, followed by trajectory-tracking experiments using the manifold deformation control method. Results from simulation and real experiments show minimal error in tracking, demonstrating the effectiveness of the control method. Finally, the actual coating thickness sprayed by the 7-axis suspended robotic arm at four locations on the motorcycle shell was measured. The results show that the measured values at each location fall within the standard range provided by the manufacturer, demonstrating consistency in spraying across different regions. This consistency highlights the precision and effectiveness of the robotic arm’s control system in achieving uniform coating thickness, even on complex and curved surfaces. Therefore, the robotic arm has been successfully applied in a factory’s automated spraying production line.